Trophoblast gene expression: Transcription factors in the specification of early trophoblast - Ezashi Toshihiko; Roberts R Michael; Das Padmalaya (BMC, 2004)
Abstract A zone of trophoblast specification is established when the embryo is amorula, presumably reflecting a unique combination of transcription factors in that zone of cells and the influence of various environmental cues and growth factors on them. A key first step in this process of specification is the down-regulation of Oct4, a transcription factor that acts as a negative regulator of trophoblast specification and of genes normally up-regulated as the trophectoderm first forms. The transcription factors believed to have a positive association with trophectoderm specification have been inferred primarily in two ways: by their expression patterns in embryos, ES cells and TS cells and by the consequences of gene disruption on embryonic development. Many of these transcription factors also control the expression of genes characteristically expressed in trophoblast but not in the epiblast, primitive endoderm and their derivatives. ES and TS cells from the mouse and other species are beginning to provide insights into the changes in gene expression that accompany lineage specification and the subsequent post-specification events that lead to functional trophoblast derivatives.